More pontoniine shrimps (Crustacea: Decapoda: Palaemonidae) from the CReefs 2009 Heron Island expedition - Bruce, A. J. (Zootaxa, 2010)
Recent collections of pontoniine shrimps from Heron Island, southern Great Barrier Reef, have provided additions to the Australian marine fauna. More material is now available indicating further taxa can be added to the Heron Island pontoniine fauna species list. Periclimenaeus heronensis sp. nov., probably a sponge associate, and P. creefi sp. nov., probably an ascidian associate, are described and illustrated. Additional records are provided of Onycocaris spinosa Fujino & Miyake and Periclimenaeus pachydentatus Bruce. Comments are also provided on the morphology of Periclimenaeus usitatus Bruce.